Implementation of Religious-Based Madrasah Performance Management For Improving Student's Akhlakul Karimah at Madrasah Aliyah - Riswan Riswan; Sutaryat Trisnamansyah; Hanafiah Hanafiah; Sofyan Sauri (Green Publisher Indonesia, 2021)
This study aims to find out and obtain a holistic description of the implementation of religious-based madrasa performance management to improve the morality of MAN students. This study uses a qualitative approach with case study research methods. The analysis was processed by interviews, observations and document studies with triangulation of sources from the Head of the Madrasah Education Section, Pokjawas, Madrasah Committee, head of MAN 4, Wakamad Akademik, teacher and student councils. The results show that efforts to overcome various problems of performance management of religious-based madrasas to improve morality can be done by separating the curriculum system that applies to the Religious Program MAN and the regular MAN. The conclusion of this study, namely the implementation of religious-based madrasa performance management for improving the morality of students at MAN 4 Banjar was carried out based on guidelines from the Ministry of Religion, but not yet effective and touching for improving the morality of students.